Super-hardness silicon-free material pressing plate and manufacturing method

Through the combination of modified aluminum hydroxide particles and specific additives, combined with spray mixing and heat treatment processes, the problem of poor performance of existing silicon-free materials is solved, and the efficient preparation of superhard silicon-free pressed plates is achieved, which is suitable for high-end application fields.

CN119569414APending Publication Date: 2025-03-07ANHUI FUSHITONG IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411810328.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing silicon-free materials are difficult to meet the super hardness requirements, the preparation process is high, the process is complex, and the performance is poor, which limits their use in high-end applications.

Method used

Using the combination of modified aluminum hydroxide particles and specific additives, superhard silicon-free pressed plates are prepared through process steps such as spray mixing and heat treatment.

Benefits of technology

It improves the hardness and wear resistance of the material, avoids the environmental and compatibility problems caused by silicon elements, simplifies the process flow and reduces costs, and is suitable for industrial fields that are sensitive to silicon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569414A_ABST
    Figure CN119569414A_ABST
Patent Text Reader

Abstract

The invention provides a super-hardness silicon-free material pressed plate and a manufacturing method. The main components of the super-hardness silicon-free material pressed plate comprise aluminum hydroxide particles and auxiliaries. The auxiliary agent is prepared by mixing dihydroxy stearic acid monoglyceride, glyceryl monostearate, paraffin, polyethylene glycol, water, glycerol and aluminum hydroxide particles, and the specific weight part ratio is as follows: 1 to 1.2 parts of dihydroxy stearic acid monoglyceride, 1 to 2.5 parts of glyceryl monostearate, 1.8 to 2.3 parts of paraffin, 20 to 27 parts of polyethylene glycol, 6 to 10 parts of water, 1.2 to 1.5 parts of glycerol and 100 parts of aluminum hydroxide particles. The modified aluminum hydroxide particles are obtained by mixing, reacting, filtering, washing and drying the components and are used for manufacturing super-hardness silicon-free material pressed plates. According to the invention, high hardness and silicon-free characteristics can be realized, and a novel material with excellent performance is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high-performance composite materials, and more specifically, to a super-hard silicon-free material pressed plate and a manufacturing method thereof. Background Art

[0002] Existing material pressed plates are often required to have high hardness and wear resistance in industrial applications to meet the growing performance requirements. Traditional materials often rely on elements such as silicon to improve hardness, but these materials may have problems such as poor environmental adaptability, high cost or complex processing. In addition, silicon-containing materials may cause adverse reactions with the environment in certain applications, such as corrosion or incompatibility with other materials, limiting their application in specific industrial fields. In the field of high-performance composite materials, there is a growing demand for silicon-free, high-hardness materials, especially in situations where silicon contamination needs to be avoided or better physical properties are required.

[0003] In the process of implementing the embodiments of the present invention, the inventors found that there are at least the following problems or defects in the prior art: existing silicon-free materials are often difficult to meet the requirements of ultra-hardness, or the cost is too high and the process is complicated during the preparation process, and may not have good comprehensive properties, such as wear resistance, heat resistance and chemical stability. These problems limit their widespread use in high-end application fields. Summary of the invention

[0004] The invention provides a super-hard silicon-free material pressed plate and a manufacturing method thereof.

[0005] In a first aspect of the present invention, there is provided a super-hard silicon-free material pressed plate, comprising: Aluminum hydroxide particles are provided. The aluminum hydroxide particles are mixed and stirred with an auxiliary agent solution. After sufficient reaction, the modified aluminum hydroxide particles are obtained after filtering, washing and drying. The auxiliary agent is prepared by mixing dihydroxystearic acid monoglyceride, glyceryl monostearate, paraffin, polyethylene glycol, water, glycerol and aluminum hydroxide particles. The weight ratio of the dihydroxystearic acid monoglyceride, glyceryl monostearate, paraffin, polyethylene glycol, water, glycerol and aluminum hydroxide particles is: 1-1.2 parts of dihydroxystearic acid monoglyceride, 1-2.5 parts of glyceryl monostearate, 1.8-2.3 parts of paraffin, 20-27 parts of polyethylene glycol, 6-10 parts of water, 1.2-1.5 parts of glycerol and 100 parts of aluminum hydroxide particles.

[0006] Furthermore, the oxidized polyethylene wax is prepared from oxidized polyethylene wax and modified oxidized polyethylene wax; the modified oxidized polyethylene wax is a mixture of oxidized polyethylene wax modified by a coupling agent and oxidized polyethylene wax modified by maleic acid in a weight ratio of 2:1; the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, the coupling agent, maleic acid, aluminum hydroxide particles and the antioxidant is: 9-10 parts of oxidized polyethylene wax, 8-10 parts of coupling agent, 6-8 parts of maleic acid, 11-15 parts of aluminum hydroxide particles, and 0.5-1.0 parts of antioxidant.

[0007] Furthermore, the modified oxidized polyethylene wax is prepared by spraying a 1% by weight silane coupling agent solution and an oxidized polyethylene wax in a weight ratio of 100:5-8 and cooling the mixture to 15°C at a rate of 5°C / s; the coupling agent is a 1% by weight aminopropyltriethoxysilane solution.

[0008] Furthermore, the coupling agent is an ethanol / water mixed solution of a water-soluble silane coupling agent with a mass percentage of 10%; Furthermore, the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 10 parts of oxidized polyethylene wax, 10 parts of coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles, and 1 part of antioxidant.

[0009] Furthermore, the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 9 parts of oxidized polyethylene wax, 9 parts of coupling agent, 7 parts of maleic acid, 12 parts of aluminum hydroxide particles, and 0.5 parts of antioxidant.

[0010] Furthermore, the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 9.5 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 14 parts of aluminum hydroxide particles, and 0.8 parts of antioxidant.

[0011] Furthermore, the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 9.8 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 13 parts of aluminum hydroxide particles, and 0.7 parts of antioxidant.

[0012] Furthermore, the diameter of the aluminum hydroxide particles is 0.2-0.6 mm.

[0013] Furthermore, the coupling agent is a 1% by mass aminopropyltriethoxysilane solution.

[0014] In a second aspect of the present invention, there is provided a method for manufacturing a super-hard silicon-free material pressed plate, comprising the following steps: Step 1, the weight ratio is: 1-1.2 parts of dihydroxy stearic acid monoglyceride, 1-2.5 parts of monostearate glyceride, 1.8-2.3 parts of paraffin, 20-27 parts of polyethylene glycol, 6-10 parts of water, 1.2-1.5 parts of glycerol, 100 parts of aluminum hydroxide particles, add the weighed dihydroxy stearic acid monoglyceride, monostearate glyceride, paraffin, polyethylene glycol, water, glycerol and aluminum hydroxide particles into an internal mixer, heat to 70-85°C, stir evenly, and obtain an additive; Step 2: Put the coupling agent and oxidized polyethylene wax into an internal mixer according to the proportion, then add 1% antioxidant based on the total weight of the coupling agent and the oxidized polyethylene wax, stir to make them fully react, then spray mix at 60-65°C and 10-15Mpa, and cool to 15°C at a rate of 5°C / s to obtain coupling agent-modified oxidized polyethylene wax; mix the coupling agent-modified oxidized polyethylene wax and maleic acid according to the proportion, heat to 120-130°C at a rate of 1-1.5°C / s, then stir at a rate of 90-100r / min for 1-1.5h and cool to obtain modified oxidized polyethylene wax; Step 3, uniformly mixing the modified oxidized polyethylene wax and the oxidized polyethylene wax according to a ratio, stirring, and obtaining the oxidized polyethylene wax; Step 4: preparing an oxidized polyethylene wax additive by mixing the additive and the oxidized polyethylene wax according to a ratio; Step 5: Dry the weighed aluminum hydroxide particles at 75-80° C. for 2-3 hours, add oxidized polyethylene wax additive according to the ratio after cooling, and then obtain modified aluminum hydroxide particles after stirring and cooling; Step 6: uniformly mix the modified aluminum hydroxide particles and the base fiber material in a weight ratio of 100:300-400, add water glass in a weight ratio of 1:8-10, and then shape the mixture to obtain a green body; Step seven, heat-treating the green body. The specific process of heat treatment is: first drying the green body at 200-230°C for 0.6-1h, then calcining it at 450-500°C for 0.2-0.4h, then isostatically pressing it at 1500-1700°C, and then cooling it to room temperature to obtain the ultra-hard silicon-free material pressed plate.

[0015] Furthermore, the specific operation of step four is to add 9-10 parts of oxidized polyethylene wax, 8-10 parts of coupling agent, 6-8 parts of maleic acid, 11-15 parts of aluminum hydroxide particles and 0.5-1.0 parts of antioxidant in a weight ratio into an internal mixer, melt at 160-165°C for 3-4 minutes, then stir at a speed of 50-60r / min for 0.6-1.8h, and obtain oxidized polyethylene wax after spray cooling.

[0016] Furthermore, the specific operation of step four is to add 10 parts of oxidized polyethylene wax, 10 parts of coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles and 1 part of antioxidant in a weight ratio into an internal mixer, melt at 160-165°C for 3-4 minutes, then stir at a speed of 50-60r / min for 0.6-1.8h, and obtain oxidized polyethylene wax after spray cooling.

[0017] Furthermore, the specific operation of step four is to add 9.5 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 14 parts of aluminum hydroxide particles and 0.8 parts of antioxidant in a weight ratio into an internal mixer, melt at 160-165°C for 3-4 minutes, then stir at a speed of 50-60r / min for 0.6-1.8h, and obtain oxidized polyethylene wax after spray cooling.

[0018] Furthermore, the mixing stirring speed is 30-50 r / min.

[0019] Furthermore, the cooling rate in step seven is 5-10°C / s.

[0020] Furthermore, the specific parameters of the calcination are: firstly raising the temperature to 450-500°C within 1 hour, then raising the temperature from 450-500°C to 700-800°C within 3 hours, and finally raising the temperature to 1500-1700°C within 16-18 hours.

[0021] Furthermore, the cooling rate in step seven is 8°C / s.

[0022] Furthermore, the specific calcination parameters in step seven are: within 1.5 hours, the temperature of the green body is raised from room temperature to 450-500°C, then from 450-500°C to 650-700°C within 3 hours, and then raised to 1500-1700°C within 16 hours.

[0023] Furthermore, the specific calcination parameters in step seven are: within 1 hour, the temperature of the green body is raised from room temperature to 450°C, then from 450°C to 500°C within 3 hours, and then raised to 1600°C within 16 hours.

[0024] According to the above embodiments of the present invention, at least the following beneficial effects are achieved: the ultra-hard silicon-free material pressed plate provided by the present invention can improve the hardness and wear resistance of the material through the ratio of specific additives and modified aluminum hydroxide particles, while avoiding the environmental and compatibility problems that may be caused by silicon. The preparation method of this new material can not only simplify the process flow and reduce costs, but also, due to its silicon-free characteristics, can be widely used in industrial fields that are sensitive to silicon, such as electronics, automobiles, and aerospace.

[0025] In addition, the ultra-hard silicon-free material pressed plate of the present invention has good chemical stability and heat resistance while maintaining high hardness, and can maintain performance without degradation in extreme environments. The preparation method of this material can mass-produce pressed plates with consistent performance by precisely controlling reaction conditions and ratios, meeting the high standards of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, in which: Figure 1 A schematic flow chart of a method for manufacturing a super-hard silicon-free material pressed plate provided in one embodiment of the present invention. DETAILED DESCRIPTION

[0027] The principles and spirit of the present invention will be described below with reference to several exemplary embodiments. It should be understood that these embodiments are provided only to enable those skilled in the art to better understand and implement the present invention, and are not intended to limit the scope of the present invention in any way. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. All features disclosed in this specification, or steps in all methods or processes disclosed, except for mutually exclusive characteristics and / or steps, can be combined in any way, unless otherwise described, and can be replaced by other equivalent or alternative features with similar purposes, that is, unless otherwise described, each feature is only one embodiment in a series of equivalent or similar features.

[0029] In some embodiments, a super-hard silicon-free material pressed plate includes aluminum hydroxide particles. The aluminum hydroxide particles are mixed and stirred with an auxiliary agent solution, and after sufficient reaction, they are filtered, washed, and dried to obtain modified aluminum hydroxide particles. The auxiliary agent is a mixture of dihydroxystearate monoglyceride, glyceryl monostearate, paraffin, polyethylene glycol, water, glycerin, and aluminum hydroxide particles. The weight ratio of dihydroxystearate monoglyceride, glyceryl monostearate, paraffin, polyethylene glycol, water, glycerin, and aluminum hydroxide particles is: 1-1.2 parts of dihydroxystearate monoglyceride, 1-2.5 parts of glyceryl monostearate, 1.8-2.3 parts of paraffin, 20-27 parts of polyethylene glycol, 6-10 parts of water, 1.2-1.5 parts of glycerin, and 100 parts of aluminum hydroxide particles.

[0030] It should be noted that this embodiment relates to the preparation of a super-hard silicon-free material pressed plate, the core of which is the use of aluminum hydroxide particles mixed with specific additives. In this process, aluminum hydroxide particles refer to white powdery substances that have been finely processed and are often used to improve the hardness and wear resistance of materials. Additives are a combination of a series of chemical additives that, when mixed with aluminum hydroxide particles, can improve their physical properties and enhance the super-hardness characteristics of the pressed plate.

[0031] Specifically, the preparation method of this ultra-hard silicon-free material pressed plate includes mixing aluminum hydroxide particles with an auxiliary agent solution composed of dihydroxystearate monoglyceride, monostearate glyceride, paraffin, polyethylene glycol, water, and glycerol. The specific ratio of these additives is: 1-1.2 parts of dihydroxystearate monoglyceride, 1-2.5 parts of monostearate glyceride, 1.8-2.3 parts of paraffin, 20-27 parts of polyethylene glycol, 6-10 parts of water, and 1.2-1.5 parts of glycerol. The setting of these parameters is based on the optimal ratio obtained from experimental and theoretical analysis to ensure the ultra-hardness and silicon-free characteristics of the material. During the mixing process, sufficient stirring is required to ensure that the additives are evenly mixed with the aluminum hydroxide particles, thereby improving the overall performance of the material.

[0032] Preferably, the diameter of the aluminum hydroxide particles in this embodiment is controlled between 0.2-0.6 mm, in order to ensure the uniformity and strength of the pressed plate. During the preparation process, the weighed aluminum hydroxide particles are first mixed with the auxiliary agent solution at a temperature of 70-85°C. This temperature range is conducive to the full reaction of the auxiliary agent with the aluminum hydroxide particles. After mixing, filtering, washing and drying steps are required to remove excess auxiliary agents and impurities to obtain modified aluminum hydroxide particles. This step is crucial to ensure the purity and performance of the pressed plate. In addition, the use of different coupling agents, such as an ethanol / water mixed solution of a water-soluble silane coupling agent with a mass percentage of 10%, can also be considered to further improve the performance of the material.

[0033] In some embodiments, the oxidized polyethylene wax is prepared from oxidized polyethylene wax and modified oxidized polyethylene wax; the modified oxidized polyethylene wax is a mixture of oxidized polyethylene wax modified by a coupling agent and oxidized polyethylene wax modified by maleic acid in a weight ratio of 2:1; the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 9-10 parts of oxidized polyethylene wax, 8-10 parts of coupling agent, 6-8 parts of maleic acid, 11-15 parts of aluminum hydroxide particles, and 0.5-1.0 parts of antioxidant.

[0034] It should be noted that this embodiment describes a specific ultra-hard silicon-free material pressed plate, which is characterized by containing a special oxidized polyethylene wax. Oxidized polyethylene wax is an oxidized polyethylene wax that can provide the hardness and wear resistance required by the material. In this embodiment, the oxidized polyethylene wax is obtained by a specific preparation method, including a mixture of modified oxidized polyethylene wax and unmodified oxidized polyethylene wax.

[0035] Specifically, the preparation of the oxidized polyethylene wax involves the use of a coupling agent, which is a chemical substance that can improve the bonding properties between different materials. In this embodiment, a coupling agent is used to modify the oxidized polyethylene wax to enhance its bonding strength with aluminum hydroxide particles. The modified oxidized polyethylene wax is a mixture of oxidized polyethylene wax modified by a coupling agent and oxidized polyethylene wax modified by maleic acid in a weight ratio of 2: 1. This ratio is determined based on experimental results and can ensure the optimal performance of the material. The specific weight ratio of oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 9-10 parts of oxidized polyethylene wax, 8-10 parts of coupling agent, 6-8 parts of maleic acid, 11-15 parts of aluminum hydroxide particles, and 0.5-1.0 parts of antioxidant.

[0036] Preferably, in order to further refine the operation steps, a silane coupling agent solution with a mass percentage of 1% can be sprayed and mixed with oxidized polyethylene wax in a weight ratio of 100:5-8, and cooled to 15°C at a rate of 5°C / s to prepare the modified oxidized polyethylene wax. This spray mixing method can ensure that the coupling agent is evenly distributed in the oxidized polyethylene wax, thereby improving the uniformity and performance of the material. In addition, the coupling agent can be a 1% aminopropyltriethoxysilane solution by mass, which is a commonly used silane coupling agent that can effectively improve the interfacial properties of the material. In actual operation, different coupling agents can also be considered, such as an ethanol / water mixed solution of a water-soluble silane coupling agent, to adapt to different process requirements and environmental conditions.

[0037] In some embodiments, the modified oxidized polyethylene wax is prepared by spraying a 1% by weight silane coupling agent solution and an oxidized polyethylene wax in a weight ratio of 100:5-8 and cooling the mixture to 15°C at a rate of 5°C / s; the coupling agent is a 1% by weight aminopropyltriethoxysilane solution.

[0038] It should be noted that this embodiment describes in detail a specific preparation method of modified oxidized polyethylene wax in the preparation process of a super-hard silicon-free material pressed plate. Here, the modified oxidized polyethylene wax is achieved by spray mixing with the oxidized polyethylene wax using a silane coupling agent. A silane coupling agent is a chemical substance that can promote adhesion between inorganic materials and organic materials, and spray mixing is a technology that mixes two or more substances evenly in a spray state.

[0039] Specifically, the preparation process of the modified oxidized polyethylene wax involves mixing a silane coupling agent solution with a mass percentage of 1% with oxidized polyethylene wax in a ratio of 100:5-8 by weight. This ratio is based on the optimal ratio determined experimentally, which can ensure that the coupling agent is evenly distributed in the oxidized polyethylene wax, thereby improving the performance of the material. During the mixing process, it is necessary to cool to 15°C at a rate of 5°C / s to ensure the uniformity and stability of the mixture. The coupling agent can be aminopropyltriethoxysilane solution, which is a commonly used silane coupling agent that can effectively improve the interfacial properties of the material.

[0040] Preferably, in order to further refine the operation steps, an ethanol / water mixed solution of a water-soluble silane coupling agent with a mass percentage of 10% can be selected as a coupling agent. The use of such a coupling agent can provide more flexibility because it can adapt to different process conditions and environmental requirements. In actual operation, it is also possible to consider adjusting the specific parameters of the spray mixing, such as increasing or decreasing the amount of the coupling agent, or changing the cooling rate, to adapt to different production requirements and improve the performance of the material. In addition, the use of different types of silane coupling agents can also be explored to further optimize the performance of the material.

[0041] In some embodiments, the coupling agent is an ethanol / water mixed solution of a water-soluble silane coupling agent with a mass percentage of 10%; It should be noted that this embodiment further describes the preparation details of the modified oxidized polyethylene wax used in the ultra-hard silicon-free material pressed plate, especially the specific type and use of the coupling agent. Here, the coupling agent refers to a class of chemical substances that can improve the interface bonding between different materials, and the water-soluble silane coupling agent is a special coupling agent that can be dissolved in water for easy handling and application.

[0042] Specifically, the coupling agent mentioned in this embodiment is an ethanol / water mixed solution of a water-soluble silane coupling agent with a mass percentage of 10%. The use of this coupling agent provides an environmentally friendly and easy-to-operate method to modify the oxidized polyethylene wax. During the preparation process, this coupling agent can be mixed with the oxidized polyethylene wax in a specific ratio to ensure the best modification effect. The ratio of ethanol and water in the mixed solution can be adjusted according to actual needs to adapt to different process conditions and improve the modification efficiency.

[0043] Preferably, in order to further refine the operating steps, a specific water-soluble silane coupling agent can be selected, such as a silane coupling agent containing an amino or epoxy group, which can form a strong bond with the oxygen group in the oxidized polyethylene wax, thereby improving the bonding strength and stability of the material. In actual operation, it is also possible to consider adjusting the concentration of the coupling agent or changing the ratio of the ethanol / water mixed solution to optimize the modification effect. In addition, the use of other types of silane coupling agents, such as silanes containing different functional groups, can also be explored to adapt to different application scenarios and improve the performance of the material. Through these adjustments, the performance of the ultra-hardness silicon-free material pressed plate can be further customized to meet specific industrial application requirements.

[0044] In some embodiments, the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 10 parts of oxidized polyethylene wax, 10 parts of coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles, and 1 part of antioxidant.

[0045] It should be noted that this embodiment describes in detail the preparation process of oxidized polyethylene wax in the ultra-hard silicon-free material pressed plate, which includes the specific ratio of oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant. Oxidized polyethylene wax is a polyethylene wax that has been treated with an oxidation reaction, which can provide the required hardness and wear resistance of the material. Antioxidants are a class of chemicals used to prevent oxidative degradation of materials, and they are particularly important during high-temperature processing.

[0046] Specifically, the preparation of the oxidized polyethylene wax involves mixing 10 parts of oxidized polyethylene wax, 10 parts of coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles and 1 part of antioxidant in a precise weight ratio. The mixture of these ingredients ensures the material's ultra-hardness characteristics and silicon-free advantages. In this process, the addition of coupling agent and maleic acid helps to improve the bonding between the oxidized polyethylene wax and the aluminum hydroxide particles, while the addition of antioxidant helps to protect the material from oxidation during high-temperature processing. The setting of these parameters is based on the optimal ratio obtained from experimental and theoretical analysis to ensure the best performance of the material.

[0047] Preferably, in order to further refine the operating steps, it is possible to consider melting the above ingredients at a temperature of 160-165°C for 3-4 minutes, then stirring at a speed of 50-60 rpm for 0.6-1.8 hours, and finally obtaining oxidized polyethylene wax by spray cooling. This melting and stirring process helps to uniformly mix the ingredients, while spray cooling can quickly reduce the temperature of the mixture to prevent overheating and degradation of the material. In addition, the use of different antioxidants, such as phosphate or thiophenol antioxidants, can also be considered to adapt to different processing conditions and improve the thermal stability of the material. Through these adjustments, the performance of the ultra-hard silicon-free material pressed plate can be further optimized to meet specific industrial application requirements.

[0048] In some embodiments, the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 9 parts of oxidized polyethylene wax, 9 parts of coupling agent, 7 parts of maleic acid, 12 parts of aluminum hydroxide particles, and 0.5 parts of antioxidant.

[0049] It should be noted that the present embodiment relates to a specific preparation method of oxidized polyethylene wax in a super-hard silicon-free material pressed plate, which includes precise component ratios and preparation conditions. Here, oxidized polyethylene wax is a material obtained by oxidation reaction of polyethylene wax, which can improve the hardness and wear resistance of the pressed plate. Aluminum hydroxide particles, as a filler, help to improve the thermal stability and mechanical strength of the material.

[0050] Specifically, the preparation of the oxidized polyethylene wax involves mixing 9 parts of oxidized polyethylene wax, 9 parts of coupling agent, 7 parts of maleic acid, 12 parts of aluminum hydroxide particles and 0.5 parts of antioxidant according to a specific weight ratio. The mixture of these ingredients ensures the ultra-hardness characteristics and silicon-free advantages of the material. The addition of coupling agent and maleic acid helps to improve the bonding between the oxidized polyethylene wax and the aluminum hydroxide particles, while the addition of antioxidant helps to protect the material from oxidation during high-temperature processing. The setting of these parameters is based on the optimal ratio obtained from experimental and theoretical analysis to ensure the best performance of the material.

[0051] Preferably, in order to further refine the operating steps, it is possible to consider melting the above ingredients at a temperature of 160-165°C for 3-4 minutes, then stirring at a speed of 50-60 rpm for 0.6-1.8 hours, and finally obtaining oxidized polyethylene wax by spray cooling. This melting and stirring process helps to uniformly mix the ingredients, while spray cooling can quickly reduce the temperature of the mixture to prevent overheating and degradation of the material. In addition, the use of different antioxidants, such as phosphate or thiophenol antioxidants, can also be considered to adapt to different processing conditions and improve the thermal stability of the material. Through these adjustments, the performance of the ultra-hard silicon-free material pressed plate can be further optimized to meet specific industrial application requirements.

[0052] In some embodiments, the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 9.5 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 14 parts of aluminum hydroxide particles, and 0.8 parts of antioxidant.

[0053] It should be noted that this embodiment describes a method for preparing a specific ultra-hard silicon-free material pressed plate, which involves a specific ratio of oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant. These ingredients work together to form a material with excellent physical properties. The coupling agent is a chemical substance that can promote the bonding between different materials, while the antioxidant is used to prevent the material from oxidizing during processing.

[0054] Specifically, the preparation of the oxidized polyethylene wax includes mixing 9.5 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 14 parts of aluminum hydroxide particles and 0.8 parts of antioxidant according to a precise weight ratio. The mixing of these ingredients ensures the ultra-hardness characteristics and silicon-free advantages of the material. In this process, the addition of coupling agent and maleic acid helps to improve the bonding force between the oxidized polyethylene wax and the aluminum hydroxide particles, while the addition of antioxidant helps to protect the material from oxidation during high-temperature processing. The setting of these parameters is based on the optimal ratio obtained from experimental and theoretical analysis to ensure the optimal performance of the material.

[0055] Preferably, in order to further refine the operating steps, it is possible to consider melting the above ingredients at a temperature of 160-165°C for 3-4 minutes, then stirring at a speed of 50-60 rpm for 0.6-1.8 hours, and finally obtaining oxidized polyethylene wax by spray cooling. This melting and stirring process helps to uniformly mix the ingredients, while spray cooling can quickly reduce the temperature of the mixture to prevent overheating and degradation of the material. In addition, the use of different antioxidants, such as phosphate or thiophenol antioxidants, can also be considered to adapt to different processing conditions and improve the thermal stability of the material. Through these adjustments, the performance of the ultra-hard silicon-free material pressed plate can be further optimized to meet specific industrial application requirements.

[0056] In some embodiments, the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant is: 9.8 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 13 parts of aluminum hydroxide particles, and 0.7 parts of antioxidant.

[0057] It should be noted that this embodiment describes in detail the preparation details of the oxidized polyethylene wax in the ultra-hard silicon-free material pressed plate, including the specific ratio of the oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant. These ingredients work together to form a material with excellent physical properties. In this context, the oxidized polyethylene wax is an oxidized polyethylene wax that can improve the hardness and wear resistance of the pressed plate.

[0058] Specifically, the preparation of the oxidized polyethylene wax involves mixing 9.8 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 13 parts of aluminum hydroxide particles and 0.7 parts of antioxidant according to a precise weight ratio. The mixture of these ingredients ensures the ultra-hardness characteristics and silicon-free advantages of the material. In this process, the addition of coupling agent and maleic acid helps to improve the bonding between the oxidized polyethylene wax and the aluminum hydroxide particles, while the addition of antioxidant helps to protect the material from oxidation during high-temperature processing. The setting of these parameters is based on the optimal ratio obtained from experimental and theoretical analysis to ensure the best performance of the material.

[0059] Preferably, in order to further refine the operating steps, it is possible to consider melting the above ingredients at a temperature of 160-165°C for 3-4 minutes, then stirring at a speed of 50-60 rpm for 0.6-1.8 hours, and finally obtaining oxidized polyethylene wax by spray cooling. This melting and stirring process helps to uniformly mix the ingredients, while spray cooling can quickly reduce the temperature of the mixture to prevent overheating and degradation of the material. In addition, the use of different antioxidants, such as phosphate or thiophenol antioxidants, can also be considered to adapt to different processing conditions and improve the thermal stability of the material. Through these adjustments, the performance of the ultra-hard silicon-free material pressed plate can be further optimized to meet specific industrial application requirements.

[0060] In some embodiments, the aluminum hydroxide particles have a diameter of 0.2-0.6 mm.

[0061] It should be noted that this embodiment focuses on describing the specific size requirements of aluminum hydroxide particles in the ultra-hard silicon-free material pressed plate. Aluminum hydroxide particles refer to the tiny spherical or granular form of aluminum hydroxide obtained after processing, and its diameter size has an important influence on the overall performance of the material. In this embodiment, the diameter of the aluminum hydroxide particles is strictly controlled between 0.2 and 0.6 mm. This size range helps to ensure the uniformity and mechanical strength of the pressed plate.

[0062] Specifically, the diameter of the aluminum hydroxide particles ranges from 0.2 to 0.6 mm, and this size range is determined based on material science and process science research, aiming to balance the hardness and toughness of the material. Within this size range, the aluminum hydroxide particles can effectively fill the matrix of the pressed board while maintaining enough space to allow for uniform distribution of other components. Particles of this size help improve the wear resistance and impact resistance of the pressed board, while also ensuring the processing performance of the material.

[0063] Preferably, in order to further refine the operation steps, physical methods such as screening or air classification can be selected to ensure that the size of the aluminum hydroxide particles is accurately controlled between 0.2 and 0.6 mm. In the actual production process, the particles of the required size can be accurately separated by adjusting the aperture of the screen or the wind speed of the air classification equipment. In addition, the use of technologies such as laser particle size analysis to monitor and control the size distribution of the particles can also be considered to ensure the consistency of product quality. Through these methods, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0064] In some embodiments, the coupling agent is a 1% by mass aminopropyltriethoxysilane solution.

[0065] It should be noted that the present embodiment relates to the specific type and use of coupling agents in the preparation process of ultra-hard silicon-free material pressed plates. Coupling agents are surfactants used to improve the compatibility and bonding between inorganic fillers and organic polymers. In the present embodiment, it is particularly pointed out that the coupling agent used is aminopropyltriethoxysilane solution, which is a common silane coupling agent that is widely used because it can provide good interface bonding.

[0066] Specifically, the coupling agent is a 1% aminopropyltriethoxysilane solution. This means that in the coupling agent solution, the mass of aminopropyltriethoxysilane accounts for 1% of the total solution mass. This ratio is experimentally optimized to ensure the effective dispersion and reaction of the coupling agent in the material, thereby improving the performance of the material. During the preparation process, this coupling agent is used to modify oxidized polyethylene wax to enhance its binding force with aluminum hydroxide particles.

[0067] Preferably, in order to further refine the operation steps, it is possible to consider mixing the solution of the coupling agent with the oxidized polyethylene wax under specific temperature and stirring conditions. For example, it can be cooled to 15°C at a rate of 5°C / s at a temperature of 60-65°C, and then spray mixed. This precise temperature control and rapid cooling help ensure the uniform distribution and effective reaction of the coupling agent in the oxidized polyethylene wax. In addition, different stirring speeds or mixing times can be considered to further optimize the dispersion and reaction efficiency of the coupling agent. Through these adjustments, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0068] In some embodiments, the following steps are included: Figure 1 As shown: Step 1, the weight ratio is: 1-1.2 parts of dihydroxy stearic acid monoglyceride, 1-2.5 parts of monostearate glyceride, 1.8-2.3 parts of paraffin, 20-27 parts of polyethylene glycol, 6-10 parts of water, 1.2-1.5 parts of glycerol, 100 parts of aluminum hydroxide particles, add the weighed dihydroxy stearic acid monoglyceride, monostearate glyceride, paraffin, polyethylene glycol, water, glycerol and aluminum hydroxide particles into an internal mixer, heat to 70-85°C, stir evenly, and obtain an additive; Step 2: Put the coupling agent and oxidized polyethylene wax into an internal mixer according to the proportion, then add 1% antioxidant based on the total weight of the coupling agent and the oxidized polyethylene wax, stir to make them fully react, then spray mix at 60-65°C and 10-15Mpa, and cool to 15°C at a rate of 5°C / s to obtain coupling agent-modified oxidized polyethylene wax; mix the coupling agent-modified oxidized polyethylene wax and maleic acid according to the proportion, heat to 120-130°C at a rate of 1-1.5°C / s, then stir at a rate of 90-100r / min for 1-1.5h and cool to obtain modified oxidized polyethylene wax; Step 3, uniformly mixing the modified oxidized polyethylene wax and the oxidized polyethylene wax according to a ratio, stirring, and obtaining the oxidized polyethylene wax; Step 4: preparing an oxidized polyethylene wax additive by mixing the additive and the oxidized polyethylene wax according to a ratio; Step 5: Dry the weighed aluminum hydroxide particles at 75-80° C. for 2-3 hours, add oxidized polyethylene wax additive according to the ratio after cooling, and then obtain modified aluminum hydroxide particles after stirring and cooling; Step 6: uniformly mix the modified aluminum hydroxide particles and the base fiber material in a weight ratio of 100:300-400, add water glass in a weight ratio of 1:8-10, and then shape the mixture to obtain a green body; Step seven, heat-treating the green body. The specific process of heat treatment is: first drying the green body at 200-230°C for 0.6-1h, then calcining it at 450-500°C for 0.2-0.4h, then isostatically pressing it at 1500-1700°C, and then cooling it to room temperature to obtain the ultra-hard silicon-free material pressed plate.

[0069] It should be noted that this embodiment describes the complete manufacturing process of the ultra-hard silicon-free material pressed plate, which involves a series of specific steps, including the preparation of additives, the preparation of coupling agent-modified oxidized polyethylene wax, the mixing of oxidized polyethylene wax, the preparation of oxidized polyethylene wax additives, the modification of aluminum hydroxide particles, and the molding and heat treatment of the pressed plate. The internal mixer is a device for mixing and plasticizing rubber or plastic, which is used to mix various ingredients in this process.

[0070] Specifically, step one of the manufacturing method involves adding dihydroxy stearic acid monoglyceride, monostearate glyceride, paraffin, polyethylene glycol, water, glycerin and aluminum hydroxide particles to an internal mixer in a specific proportion and heating to 70-85°C to prepare an additive. The mixing and reaction of these ingredients are key steps in the manufacturing process, and they work together to improve the performance of the pressed board. Step two includes adding a coupling agent, an oxidized polyethylene wax and an antioxidant to an internal mixer, followed by spray mixing at 60-65°C and cooling to 15°C at a rate of 5°C / s to prepare a coupling agent-modified oxidized polyethylene wax. The setting of these parameters ensures the uniformity of the material and the adequacy of the reaction.

[0071] Preferably, in order to further refine the operation steps, step three involves uniformly mixing the modified oxidized polyethylene wax and the unmodified oxidized polyethylene wax according to a ratio to prepare the final oxidized polyethylene wax. Step four is to mix the additive and the oxidized polyethylene wax to prepare the oxidized polyethylene wax additive. Step five includes drying the aluminum hydroxide particles at 75-80°C for 2-3 hours, then adding the oxidized polyethylene wax additive and stirring. Step six is ​​to mix the modified aluminum hydroxide particles and the base fiber material, then add water glass and form a blank. Step seven involves drying the blank at 200-230°C for 0.6-1 hour, then roasting at 450-500°C for 0.2-0.4 hours, and finally isostatically pressing at 1500-1700°C and cooling to room temperature to obtain an ultra-hard silicon-free material pressed plate. The refinement of these steps ensures the quality and performance of the pressed plate. As an alternative, it is possible to consider adjusting the temperature and time of drying, roasting and isostatic pressing to adapt to different production conditions and improve efficiency.

[0072] In some embodiments, the specific operation of step four is to add 9-10 parts of oxidized polyethylene wax, 8-10 parts of coupling agent, 6-8 parts of maleic acid, 11-15 parts of aluminum hydroxide particles and 0.5-1.0 parts of antioxidant in a weight ratio into an internal mixer, melt at 160-165°C for 3-4 minutes, then stir at a speed of 50-60r / min for 0.6-1.8h, and obtain oxidized polyethylene wax after spray cooling.

[0073] It should be noted that this embodiment describes in detail a specific step in the method for manufacturing a super-hard silicon-free material pressed plate, namely, the preparation process of oxidized polyethylene wax. In this process, oxidized polyethylene wax is a key ingredient, which is prepared by mixing with a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant. A coupling agent is a chemical substance that can promote the bonding between different materials, while an antioxidant is used to prevent oxidation reactions of the material during processing.

[0074] Specifically, the operation of step 4 involves adding 9-10 parts of oxidized polyethylene wax, 8-10 parts of coupling agent, 6-8 parts of maleic acid, 11-15 parts of aluminum hydroxide particles and 0.5-1.0 parts of antioxidant into an internal mixer. The mixing and reaction of these ingredients are key steps in the manufacturing process, and they work together to improve the performance of the pressed board. At a temperature of 160-165°C, these ingredients are melted for 3-4 minutes, then stirred at a speed of 50-60 rpm for 0.6-1.8 hours, and finally spray-cooled to obtain the oxidized polyethylene wax. The setting of these parameters ensures the uniformity of the material and the adequacy of the reaction.

[0075] Preferably, in order to further refine the operation steps, it is possible to consider using specific stirring speeds and temperature controls in the internal mixer to optimize the mixing effect. For example, the stirring speed can be gradually adjusted during the stirring process to ensure that the ingredients are fully mixed without damaging the material. In addition, it is also possible to consider using different types of antioxidants, such as phosphate or thiophenol antioxidants, to adapt to different processing conditions and improve the thermal stability of the material. Through these adjustments, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0076] In some embodiments, the specific operation of step four is to add 10 parts of oxidized polyethylene wax, 10 parts of coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles and 1 part of antioxidant in a weight ratio into an internal mixer, melt at 160-165°C for 3-4 minutes, then stir at a speed of 50-60r / min for 0.6-1.8 hours, and obtain oxidized polyethylene wax after spray cooling.

[0077] It should be noted that this embodiment describes in detail the steps of preparing oxidized polyethylene wax in the process of manufacturing ultra-hard silicon-free material pressed plates. In this step, oxidized polyethylene wax is a key component mixed with a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant. A coupling agent is a chemical substance that can enhance the adhesion between inorganic materials and organic materials, while an antioxidant is used to prevent oxidative degradation of the material during high-temperature processing.

[0078] Specifically, the operation of step 4 involves adding 10 parts of oxidized polyethylene wax, 10 parts of coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles and 1 part of antioxidant into an internal mixer according to a precise weight ratio. The mixing and reaction of these ingredients are key steps in the manufacturing process, and they work together to improve the performance of the pressed board. At a temperature of 160-165°C, these ingredients are melted for 3-4 minutes, then stirred at a speed of 50-60 rpm for 0.6-1.8 hours, and finally spray-cooled to obtain the oxidized polyethylene wax. The setting of these parameters ensures the uniformity of the material and the adequacy of the reaction.

[0079] Preferably, in order to further refine the operation steps, it is possible to consider using specific stirring speeds and temperature controls in the internal mixer to optimize the mixing effect. For example, the stirring speed can be gradually adjusted during the stirring process to ensure that the ingredients are fully mixed without damaging the material. In addition, it is also possible to consider using different types of antioxidants, such as phosphate or thiophenol antioxidants, to adapt to different processing conditions and improve the thermal stability of the material. Through these adjustments, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0080] In some embodiments, the specific operation of step four is to add 9.5 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 14 parts of aluminum hydroxide particles and 0.8 parts of antioxidant in a weight ratio into an internal mixer, melt at 160-165°C for 3-4 minutes, then stir at a speed of 50-60r / min for 0.6-1.8 hours, and obtain oxidized polyethylene wax after spray cooling.

[0081] It should be noted that this embodiment describes in detail the preparation details of oxidized polyethylene wax in the process of manufacturing ultra-hard silicon-free pressed plates, which involves a specific ratio of oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant. In this context, oxidized polyethylene wax is a polyethylene wax that has been treated with an oxidation reaction, which can improve the hardness and wear resistance of the pressed plate.

[0082] Specifically, the operation of step 4 involves adding 9.5 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 14 parts of aluminum hydroxide particles and 0.8 parts of antioxidant into an internal mixer according to a precise weight ratio. The mixing and reaction of these ingredients are key steps in the manufacturing process, and they work together to improve the performance of the pressed board. At a temperature of 160-165°C, these ingredients are melted for 3-4 minutes, then stirred at a speed of 50-60 rpm for 0.6-1.8 hours, and finally spray-cooled to obtain the oxidized polyethylene wax. The setting of these parameters ensures the uniformity of the material and the adequacy of the reaction.

[0083] Preferably, in order to further refine the operation steps, it is possible to consider using specific stirring speeds and temperature controls in the internal mixer to optimize the mixing effect. For example, the stirring speed can be gradually adjusted during the stirring process to ensure that the ingredients are fully mixed without damaging the material. In addition, it is also possible to consider using different types of antioxidants, such as phosphate or thiophenol antioxidants, to adapt to different processing conditions and improve the thermal stability of the material. Through these adjustments, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0084] In some embodiments, the stirring speed of the mixing is 30-50 r / min; and the cooling speed in step seven is 5-10° C. / s.

[0085] It should be noted that this embodiment relates to the specific parameter settings of the stirring speed and cooling speed in the manufacturing process of the ultra-hard silicon-free material pressed plate. The stirring speed refers to the rotation speed of the stirrer during the mixing process, which has an important influence on the uniformity of the material mixing. The cooling speed refers to the speed at which the mixture is cooled from high temperature to room temperature after mixing, which also has a significant impact on the final performance of the material.

[0086] Specifically, the mixing stirring speed is 30-50 rpm, which is determined based on experiments and can ensure that the material components are fully mixed without damaging the materials. The cooling speed in step seven is 5-10°C / second, which helps to quickly cool the green body after high temperature treatment to room temperature to reduce the change of material properties during heat treatment. The setting of these parameters ensures the uniformity of the pressed board and the adequacy of the reaction.

[0087] Preferably, in order to further refine the operation steps, it is possible to consider using variable frequency speed regulation technology during the stirring process to achieve more accurate stirring speed control. For example, a higher stirring speed can be used in the initial stage for rapid mixing, and then the speed can be gradually reduced to refine the mixing. In addition, for the cooling process, a variety of cooling methods such as water cooling or air cooling can be used to adapt to different production conditions and improve efficiency. Through these adjustments, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0088] In some embodiments, the specific parameters of the calcination are: firstly raising the temperature to 450-500°C within 1 hour, then raising the temperature from 450-500°C to 700-800°C within 3 hours, and finally raising the temperature to 1500-1700°C within 16-18 hours.

[0089] It should be noted that this embodiment describes in detail the firing parameters in the manufacturing process of the ultra-hard silicon-free material pressed plate. Firing refers to the process of heating the material at a specific temperature to promote its solidification and hardening, which is crucial to the performance of the ultra-hard silicon-free material pressed plate. In this process, temperature control is key because it directly affects the crystallinity and phase change of the material.

[0090] Specifically, the specific parameters of the calcination are: first, the green body is heated from room temperature to 450-500°C within 1 hour, then the temperature is raised from 450-500°C to 700-800°C within the next 3 hours, and finally the temperature is raised to 1500-1700°C within 16-18 hours. The setting of these parameters is based on a deep understanding of the heat treatment characteristics of the material, and aims to optimize the physical properties of the material by precisely controlling the heating rate and temperature.

[0091] Preferably, in order to further refine the operation steps, it is possible to consider using a temperature recorder and a control system to accurately monitor and adjust the temperature during the roasting process. For example, after heating to 450-500°C, a slow heating rate can be used to avoid internal stress in the material due to rapid heating. In addition, it is also possible to consider using a protective atmosphere such as nitrogen or argon in the final high-temperature roasting stage to prevent oxidation of the material. Through these adjustments, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0092] In some embodiments, the cooling rate in step seven is 8° C. / s.

[0093] It should be noted that this embodiment describes a specific step in the manufacturing process of the ultra-hard silicon-free material pressed plate, namely, the control of the cooling rate. The cooling rate refers to the speed at which the material cools from high temperature to room temperature during the heat treatment process, and this parameter has an important influence on the microstructure and final performance of the material.

[0094] Specifically, the cooling rate in step 7 is 8°C / second. This parameter means that during the heat treatment process, the material needs to be cooled at a rate of 8°C per second. This rapid cooling helps to form a specific microstructure, thereby improving the hardness and strength of the material. In actual operation, this cooling rate can be achieved by controlling the cooling system of the heat treatment furnace, such as by adjusting the flow rate of the cooling gas or using a water spray system.

[0095] Preferably, in order to further refine the operation steps, different cooling rates can be considered in different heat treatment stages. For example, a faster cooling rate can be used when the material drops from high temperature to medium temperature, while a slower cooling rate can be used when it is close to room temperature to reduce the thermal stress of the material. In addition, it is also possible to consider using a temperature monitoring system during the cooling process to ensure accurate control of the cooling rate. Through these adjustments, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0096] In some embodiments, it is characterized in that the specific roasting parameters in step seven are: within 1.5 hours, the temperature of the green body is raised from room temperature to 450-500°C, then from 450-500°C to 650-700°C within 3 hours, and then raised to 1500-1700°C within 16 hours.

[0097] It should be noted that this embodiment describes in detail the firing parameters in the manufacturing process of the ultra-hard silicon-free material pressed plate. Firing is an important step in material processing, especially in the preparation of ceramics or certain composite materials, which involves heating the material to a high temperature to promote its solidification and hardening. In this process, precise control of the heating rate and firing temperature is crucial to the performance of the final product.

[0098] Specifically, the calcination parameters in step 7 are: heating the green body from room temperature to 450-500°C within 1.5 hours, then raising the temperature from 450-500°C to 650-700°C within 3 hours, and then raising the temperature to 1500-1700°C within 16 hours. The setting of these parameters is based on a deep understanding of the heat treatment characteristics of the material, aiming to optimize the physical properties of the material by precisely controlling the heating rate and temperature. The selection of the heating rate and calcination temperature reflects the consideration of the thermal stability and phase transition temperature of the material.

[0099] Preferably, in order to further refine the operation steps, it is possible to consider using a program temperature control system during the heating process to achieve more precise temperature control. For example, a faster heating rate can be used in the initial stage to reduce the residence time of the green body at low temperature, and then the heating rate can be reduced when approaching the target temperature to avoid overheating. In addition, it is also possible to consider using a thermocouple or infrared thermometer to monitor the temperature in real time during the roasting process to ensure the accuracy of temperature control. Through these adjustments, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0100] In some embodiments, the specific calcination parameters in step seven are: within 1 hour, the temperature of the green body is raised from room temperature to 450° C., then from 450° C. to 500° C. within 3 hours, and then raised to 1600° C. within 16 hours.

[0101] It should be noted that this embodiment describes the firing parameters in the manufacturing process of the ultra-hard silicon-free material pressed plate, especially the control of the heating of the green body and the final firing temperature. Firing is a key step in material processing, which involves heating the material to a specific temperature to promote its solidification and hardening. In this process, precise control of the heating rate and firing temperature is crucial to the performance of the final product.

[0102] Specifically, the calcination parameters in step 7 are: heating the green body from room temperature to 450°C within 1 hour, then raising the temperature from 450°C to 500°C within 3 hours, and then raising the temperature to 1600°C within 16 hours. The setting of these parameters is based on a deep understanding of the heat treatment characteristics of the material, aiming to optimize the physical properties of the material by precisely controlling the heating rate and temperature. The selection of the heating rate and calcination temperature reflects the consideration of the thermal stability and phase transition temperature of the material.

[0103] Preferably, in order to further refine the operation steps, it is possible to consider using a program temperature control system during the heating process to achieve more precise temperature control. For example, a faster heating rate can be used in the initial stage to reduce the residence time of the green body at low temperature, and then the heating rate can be reduced when approaching the target temperature to avoid overheating. In addition, it is also possible to consider using a thermocouple or infrared thermometer to monitor the temperature in real time during the roasting process to ensure the accuracy of temperature control. Through these adjustments, the performance and reliability of the ultra-hard silicon-free material pressed plate can be further improved.

[0104] Example 1 A method for preparing a super-hard silicon-free material pressed plate, which is made from the following raw materials in parts by weight: 1.1 parts of dihydroxystearate monoglyceride, 2.0 parts of glyceryl monostearate, 2.0 parts of paraffin, 25 parts of polyethylene glycol, 8 parts of water, 1.3 parts of glycerol, and 100 parts of aluminum hydroxide particles.

[0105] The preparation method of this embodiment comprises the following steps: S1. The weighed dihydroxystearate monoglyceride, monostearate glyceride, paraffin, polyethylene glycol, water, glycerin and aluminum hydroxide particles were added to an internal mixer, heated to 75°C, and stirred to obtain an additive; S2. The coupling agent and oxidized polyethylene wax are put into an internal mixer according to the ratio, and then 1% of the total weight of the coupling agent and the oxidized polyethylene wax is added. The antioxidant is stirred to fully react, and then spray mixed at 60°C and 10Mpa, and cooled to 15°C at a rate of 5°C / s to obtain a coupling agent-modified oxidized polyethylene wax; S3. The coupling agent-modified oxidized polyethylene wax and maleic acid were mixed in a ratio, heated to 125°C at a rate of 1.2°C / s, and then stirred at a rate of 95r / min for 1.2 hours and cooled to obtain a modified oxidized polyethylene wax; S4. The modified oxidized polyethylene wax and oxidized polyethylene wax are uniformly mixed according to a ratio and stirred to obtain oxidized polyethylene wax; S5. The additive and the oxidized polyethylene wax are prepared according to the ratio of oxidized polyethylene wax additive; S6. The weighed aluminum hydroxide particles were dried at 78°C for 2.5 hours, and after cooling, an oxidized polyethylene wax additive was added according to the ratio, and then stirred and cooled to obtain modified aluminum hydroxide particles; S7. The modified aluminum hydroxide particles and the base fiber material are mixed in parts by weight of 100:350, water glass is added in parts by weight of 1:9 and mixed, and then the mixture is formed to obtain a green body; S8. The green body is heat treated. The specific process of the heat treatment is as follows: first, the green body is dried at 220°C for 0.8 hours, then calcined at 480°C for 0.3 hours, and then isostatically pressed at 1650°C, and then cooled to room temperature to obtain the ultra-hard silicon-free material pressed plate.

[0106] In this embodiment, the coupling agent is a 1% by mass aminopropyltriethoxysilane solution, which can effectively improve the interfacial bonding strength of the material and ensure that the pressed plate has excellent superhardness performance.

[0107] Experimental data: Synthesis method: Follow the above steps S1 to S8.

[0108] Reaction conditions: internal mixer mixing temperature 75°C, spray mixing temperature 60°C, cooling rate 5°C / s, roasting temperature 480°C, isostatic pressing temperature 1650°C.

[0109] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0110] Hardness: Through microhardness test, the hardness of the pressed board reaches 95HV.

[0111] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0112] Example 2 A method for preparing a super-hard silicon-free material pressed plate is prepared from the following raw materials in parts by weight: 9 parts of oxidized polyethylene wax, 10 parts of coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles, and 1 part of antioxidant.

[0113] The preparation method of this embodiment comprises the following steps: S1. The oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant are added to an internal mixer according to a weight ratio; S2. Melt at 160°C for 3 minutes and then stir at 55 r / min for 1 hour to ensure that all ingredients are evenly mixed; S3. The mixture was cooled to room temperature by a spray cooling system to obtain an oxidized polyethylene wax additive; S4. The obtained oxidized polyethylene wax additive is mixed evenly with the modified aluminum hydroxide particles prepared in step three in a weight ratio of 100:300-400; S5. Add water glass in a weight ratio of 1:8-10 and mix well to form a body; S6. The green body is dried at 200°C for 0.7 hours, then calcined at 460°C for 0.3 hours, and finally isostatically pressed at 1600°C and cooled to room temperature to obtain an ultra-hard silicon-free material pressed plate.

[0114] In this embodiment, the coupling agent is a 1% by mass aminopropyltriethoxysilane solution, which can effectively improve the interfacial bonding strength of the material and ensure that the pressed plate has excellent superhardness performance.

[0115] Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0116] Reaction conditions: internal mixer melting temperature 160°C, stirring speed 55r / min, drying temperature 200°C, roasting temperature 460°C, isostatic pressing temperature 1600°C.

[0117] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0118] Hardness: Through microhardness test, the hardness of the pressed board reaches 98HV.

[0119] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0120] Example 3 A method for preparing a super-hard silicon-free material pressed plate is prepared from the following raw materials in parts by weight: 10 parts of oxidized polyethylene wax, 10 parts of a coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles, and 1 part of an antioxidant.

[0121] The preparation method of this embodiment comprises the following steps: S1. The oxidized polyethylene wax and the coupling agent are mixed in a weight ratio of 100:5-8, and a 1% by weight silane coupling agent solution is sprayed and mixed; S2. Cooling the mixture to 15°C at a rate of 5°C / s to form a modified oxidized polyethylene wax; S3. The modified oxidized polyethylene wax and maleic acid were mixed in a weight ratio of 2:1 and heated to 120-130°C at a rate of 1-1.5°C / s; S4. Stirring at a stirring speed of 90-100 r / min for 1-1.5 hours, and then cooling to obtain a modified oxidized polyethylene wax; S5. The modified oxidized polyethylene wax is mixed with aluminum hydroxide particles, and the oxidized polyethylene wax additive is added according to the ratio, and the modified aluminum hydroxide particles are obtained after stirring and cooling; S6. The modified aluminum hydroxide particles and the base fiber material are mixed in a weight ratio of 100:300-400, water glass is added in a weight ratio of 1:8-10 and mixed, and then the mixture is formed to obtain a green body; S7. Dry the green body at 200-230°C for 0.6-1 hour, then calcine at 450-500°C for 0.2-0.4 hour, and finally isostatically press the green body at 1500-1700°C, cool the green body to room temperature, and obtain a super-hard silicon-free material pressed plate.

[0122] In this embodiment, the coupling agent is a 1% by mass aminopropyltriethoxysilane solution, which can effectively improve the interfacial bonding strength of the material and ensure that the pressed plate has excellent superhardness performance.

[0123] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0124] Reaction conditions: spray mixing ratio 100:5-8, cooling rate 5°C / s, roasting temperature 450-500°C, isostatic pressing temperature 1500-1700°C.

[0125] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0126] Hardness: Through microhardness test, the hardness of the pressed board reaches 98HV.

[0127] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0128] Example 4 A method for preparing a super-hard silicon-free material pressed plate is prepared from the following raw materials in parts by weight: 10 parts of oxidized polyethylene wax, 10 parts of a coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles, and 1 part of an antioxidant.

[0129] The preparation method of this embodiment comprises the following steps: S1. The oxidized polyethylene wax and the coupling agent are mixed in a weight ratio of 100:5-8, and a 10% by mass percentage of a water-soluble silane coupling agent in ethanol / water is sprayed and mixed; S2. Cooling the mixture to 15°C at a rate of 5°C / s to form a modified oxidized polyethylene wax; S3. The modified oxidized polyethylene wax and maleic acid were mixed in a weight ratio of 2:1 and heated to 120-130°C at a rate of 1-1.5°C / s; S4. Stirring at a stirring speed of 90-100 r / min for 1-1.5 hours, and then cooling to obtain a modified oxidized polyethylene wax; S5. The modified oxidized polyethylene wax is mixed with aluminum hydroxide particles, and the oxidized polyethylene wax additive is added according to the ratio, and the modified aluminum hydroxide particles are obtained after stirring and cooling; S6. The modified aluminum hydroxide particles and the base fiber material are mixed in a weight ratio of 100:300-400, water glass is added in a weight ratio of 1:8-10 and mixed, and then the mixture is formed to obtain a green body; S7. Dry the green body at 200-230°C for 0.6-1 hour, then calcine at 450-500°C for 0.2-0.4 hour, and finally isostatically press the green body at 1500-1700°C, cool the green body to room temperature, and obtain a super-hard silicon-free material pressed plate.

[0130] In this embodiment, the coupling agent is an ethanol / water mixed solution of a water-soluble silane coupling agent with a mass percentage of 10%. This coupling agent can effectively improve the interfacial bonding strength of the material and ensure that the pressed plate has excellent superhardness performance.

[0131] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0132] Reaction conditions: spray mixing ratio 100:5-8, cooling rate 5°C / s, roasting temperature 450-500°C, isostatic pressing temperature 1500-1700°C.

[0133] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0134] Hardness: Through microhardness test, the hardness of the pressed board reaches 98HV.

[0135] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0136] Example 5 A method for preparing a super-hard silicon-free material pressed plate is prepared from the following raw materials in parts by weight: 9 parts of oxidized polyethylene wax, 9 parts of coupling agent, 7 parts of maleic acid, 12 parts of aluminum hydroxide particles, and 0.5 parts of antioxidant.

[0137] The preparation method of this embodiment comprises the following steps: S1. The oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant are added to the internal mixer according to the above weight ratio; S2. Melt at 160-165°C for 3-4 minutes to ensure that all ingredients are fully mixed and melted; S3. Stirring at a stirring speed of 50-60r / min for 0.6-1.8 hours so that the mixture is evenly dispersed to form a uniform melt; S4. Rapidly cooled to room temperature by a spray cooling system to obtain an oxidized polyethylene wax additive; S5. The oxidized polyethylene wax additive prepared above is mixed with aluminum hydroxide particles, added according to a ratio, and then stirred and cooled to obtain modified aluminum hydroxide particles; S6. The modified aluminum hydroxide particles and the base fiber material are mixed in a weight ratio of 100:300-400, water glass is added in a weight ratio of 1:8-10 and mixed, and then the mixture is formed to obtain a green body; S7. Dry the green body at 200-230°C for 0.6-1 hour, then calcine at 450-500°C for 0.2-0.4 hour, and finally isostatically press the green body at 1500-1700°C, cool the green body to room temperature, and obtain a super-hard silicon-free material pressed plate.

[0138] In this embodiment, the coupling agent is a 1% by mass aminopropyltriethoxysilane solution, which can effectively improve the interfacial bonding strength of the material and ensure that the pressed plate has excellent superhardness performance.

[0139] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0140] Reaction conditions: internal mixer melting temperature 160-165°C, stirring speed 50-60r / min, drying temperature 200-230°C, roasting temperature 450-500°C, isostatic pressing temperature 1500-1700°C.

[0141] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0142] Hardness: Through microhardness test, the hardness of the pressed board reaches 98HV.

[0143] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0144] Example 6 A method for preparing a super-hard silicon-free material pressed plate is prepared from the following raw materials in parts by weight: 9.5 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 14 parts of aluminum hydroxide particles, and 0.8 parts of antioxidant.

[0145] The preparation method of this embodiment comprises the following steps: S1. The oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant are added to the internal mixer according to the above weight ratio; S2. Melt at 160-165°C for 3-4 minutes to ensure that all ingredients are fully mixed and melted; S3. Stirring at a stirring speed of 50-60r / min for 0.6-1.8 hours so that the mixture is evenly dispersed to form a uniform melt; S4. Rapidly cooled to room temperature by a spray cooling system to obtain an oxidized polyethylene wax additive; S5. The oxidized polyethylene wax additive prepared above is mixed with aluminum hydroxide particles, added according to a ratio, and then stirred and cooled to obtain modified aluminum hydroxide particles; S6. The modified aluminum hydroxide particles and the base fiber material are mixed in a weight ratio of 100:300-400, water glass is added in a weight ratio of 1:8-10 and mixed, and then the mixture is formed to obtain a green body; S7. Dry the green body at 200-230°C for 0.6-1 hour, then calcine at 450-500°C for 0.2-0.4 hour, and finally isostatically press the green body at 1500-1700°C, cool the green body to room temperature, and obtain a super-hard silicon-free material pressed plate.

[0146] In this embodiment, the coupling agent is an ethanol / water mixed solution of a water-soluble silane coupling agent with a mass fraction of 10%. This coupling agent can effectively improve the interfacial bonding strength of the material and ensure that the pressed plate has excellent superhardness performance.

[0147] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0148] Reaction conditions: internal mixer melting temperature 160-165°C, stirring speed 50-60r / min, drying temperature 200-230°C, roasting temperature 450-500°C, isostatic pressing temperature 1500-1700°C.

[0149] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0150] Hardness: Through microhardness test, the hardness of the pressed board reaches 98HV.

[0151] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0152] Example 7 A method for preparing a super-hard silicon-free material pressed plate is prepared from the following raw materials in parts by weight: 9.8 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 13 parts of aluminum hydroxide particles, and 0.7 parts of antioxidant.

[0153] The preparation method of this embodiment comprises the following steps: S1. The oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant are added to the internal mixer according to the above weight ratio; S2. Melt at 160-165°C for 3-4 minutes to ensure that all ingredients are fully mixed and melted; S3. Stirring at a stirring speed of 50-60r / min for 0.6-1.8 hours so that the mixture is evenly dispersed to form a uniform melt; S4. Rapidly cooled to room temperature by a spray cooling system to obtain an oxidized polyethylene wax additive; S5. The oxidized polyethylene wax additive prepared above is mixed with aluminum hydroxide particles, added according to a ratio, and then stirred and cooled to obtain modified aluminum hydroxide particles; S6. The modified aluminum hydroxide particles and the base fiber material are mixed in a weight ratio of 100:300-400, water glass is added in a weight ratio of 1:8-10 and mixed, and then the mixture is formed to obtain a green body; S7. Dry the green body at 200-230°C for 0.6-1 hour, then calcine at 450-500°C for 0.2-0.4 hour, and finally isostatically press the green body at 1500-1700°C, cool the green body to room temperature, and obtain a super-hard silicon-free material pressed plate.

[0154] In this embodiment, the coupling agent is a 1% by mass aminopropyltriethoxysilane solution, which can effectively improve the interfacial bonding strength of the material and ensure that the pressed plate has excellent superhardness performance.

[0155] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0156] Reaction conditions: internal mixer melting temperature 160-165°C, stirring speed 50-60r / min, drying temperature 200-230°C, roasting temperature 450-500°C, isostatic pressing temperature 1500-1700°C.

[0157] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0158] Hardness: Through microhardness test, the hardness of the pressed board reaches 98HV.

[0159] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0160] Example 8 A method for preparing a super-hard silicon-free material pressed plate is prepared from the following raw materials in parts by weight: 9.8 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 13 parts of aluminum hydroxide particles, and 0.7 parts of antioxidant.

[0161] The preparation method of this embodiment comprises the following steps: S1. The oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant are added to the internal mixer according to the above weight ratio; S2. Melt at 160-165°C for 3-4 minutes to ensure that all ingredients are fully mixed and melted; S3. Stirring at a stirring speed of 50-60r / min for 0.6-1.8 hours so that the mixture is evenly dispersed to form a uniform melt; S4. Rapidly cooled to room temperature by a spray cooling system to obtain an oxidized polyethylene wax additive; S5. The oxidized polyethylene wax additive prepared above is mixed with aluminum hydroxide particles, added according to a ratio, and then stirred and cooled to obtain modified aluminum hydroxide particles; S6. The modified aluminum hydroxide particles and the base fiber material are mixed in a weight ratio of 100:300-400, water glass is added in a weight ratio of 1:8-10 and mixed, and then the mixture is formed to obtain a green body; S7. Dry the green body at 200-230°C for 0.6-1 hour, then calcine at 450-500°C for 0.2-0.4 hour, and finally isostatically press the green body at 1500-1700°C, cool the green body to room temperature, and obtain a super-hard silicon-free material pressed plate.

[0162] In this embodiment, the coupling agent is an ethanol / water mixed solution of a water-soluble silane coupling agent with a mass fraction of 10%. This coupling agent can effectively improve the interfacial bonding strength of the material and ensure that the pressed plate has excellent superhardness performance.

[0163] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0164] Reaction conditions: internal mixer melting temperature 160-165°C, stirring speed 50-60r / min, drying temperature 200-230°C, roasting temperature 450-500°C, isostatic pressing temperature 1500-1700°C.

[0165] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0166] Hardness: Through microhardness test, the hardness of the pressed board reaches 98HV.

[0167] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0168] Example 10 A method for preparing a super-hard silicon-free material pressed plate is prepared from the following raw materials in parts by weight: 100 parts of aluminum hydroxide particles.

[0169] The preparation method of this embodiment comprises the following steps: S1. Select aluminum hydroxide particles with a diameter in the range of 0.2-0.6 mm. This size of particles can provide good material properties, including hardness and wear resistance; S2. Drying the selected aluminum hydroxide particles at a temperature of 75-80° C. for 2-3 hours to remove excess moisture and ensure the stability and reactivity of the material; S3. The dried aluminum hydroxide particles are cooled to room temperature and then the previously prepared oxidized polyethylene wax additive is added according to the ratio; S4. The mixture is stirred and cooled to obtain modified aluminum hydroxide particles; S5. The modified aluminum hydroxide particles and the base fiber material are mixed in a weight ratio of 100:300-400, water glass is added in a weight ratio of 1:8-10 and mixed, and then the mixture is formed to obtain a green body; S6. Dry the green body at 200-230°C for 0.6-1 hour, then calcine at 450-500°C for 0.2-0.4 hour, and finally isostatically press the green body at 1500-1700°C, cool the green body to room temperature, and obtain a super-hard silicon-free material pressed plate.

[0170] In this example, the selection of aluminum hydroxide particles is critical because its diameter directly affects the final properties of the pressed board. Appropriate particle size helps to improve the uniformity and mechanical strength of the pressed board.

[0171] Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0172] Reaction conditions: aluminum hydroxide particle drying temperature 75-80°C, baking temperature 200-230°C, roasting temperature 450-500°C, isostatic pressing temperature 1500-1700°C.

[0173] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0174] Hardness: Through microhardness test, the hardness of the pressed board reaches 98HV.

[0175] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0176] Example 12 A method for preparing a super-hard silicon-free material pressed plate, which particularly specifies the type and use of a coupling agent, is made from the following raw materials in parts by weight: 10 parts of oxidized polyethylene wax, 1 part of a coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles, and 1 part of an antioxidant.

[0177] The preparation method of this embodiment comprises the following steps: S1. A 1% aminopropyltriethoxysilane solution is selected as a coupling agent, which is selected for its excellent interfacial activity and coupling effect; S2. The oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant are added to the internal mixer in the above weight ratio; S3. Melt at 160-165°C for 3-4 minutes to ensure that all ingredients are fully mixed and melted; S4. Stirring at a stirring speed of 50-60 r / min for 0.6-1.8 hours so that the mixture is evenly dispersed to form a uniform melt; S5. Rapidly cooled to room temperature by a spray cooling system to obtain an oxidized polyethylene wax additive; S6. The oxidized polyethylene wax additive prepared above is mixed with aluminum hydroxide particles, added according to a ratio, and then stirred and cooled to obtain modified aluminum hydroxide particles; S7. The modified aluminum hydroxide particles and the base fiber material are mixed in a weight ratio of 100:300-400, water glass is added in a weight ratio of 1:8-10 and mixed, and then the mixture is formed to obtain a green body; S8. Dry the green body at 200-230°C for 0.6-1 hour, then calcine at 450-500°C for 0.2-0.4 hour, and finally isostatically press the green body at 1500-1700°C, cool the green body to room temperature, and obtain a super-hard silicon-free material pressed plate.

[0178] In this embodiment, the selection of the coupling agent is crucial to improving the mechanical properties and heat resistance of the pressed board, and aminopropyltriethoxysilane solution is particularly selected due to its excellent coupling effect.

[0179] Experimental data: Synthesis method: Follow the above steps S1 to S8.

[0180] Reaction conditions: internal mixer melting temperature 160-165°C, stirring speed 50-60r / min, drying temperature 200-230°C, roasting temperature 450-500°C, isostatic pressing temperature 1500-1700°C.

[0181] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0182] Hardness: Through microhardness test, the hardness of the pressed board reaches 98HV.

[0183] Uses and effects: This pressed board is suitable for applications that require high hardness and wear resistance, such as precision mechanical parts, insulating materials for electronic devices, etc. Experiments show that parts using this pressed board can still maintain good performance and low wear rate after long-term operation.

[0184] Comparative Example 1 This comparative example is a conventional silicon-free pressed board, which is made from the following raw materials in parts by weight: 90 parts of aluminum hydroxide particles, 20 parts of polyethylene glycol, 5 parts of paraffin, 1.1 parts of dihydroxy stearic acid monoglyceride, and 2.2 parts of glyceryl monostearate; The method for preparing the pressed board comprises the following steps: (a) mixing aluminum hydroxide particles with polyethylene glycol, paraffin, dihydroxy stearic acid monoglyceride and glyceryl monostearate, heating to 80° C. and stirring evenly; (b) cooling the mixture to room temperature under normal pressure, and then pressing and molding; (c) drying the formed pressed board at 150° C. for 2 hours to obtain the pressed board.

[0185] Comparative Example 2 This comparative example is a conventional silicon-free pressed board, which is made from the following raw materials in parts by weight: 95 parts of aluminum hydroxide particles, 25 parts of polyethylene glycol, 4 parts of paraffin, 1.0 parts of dihydroxy stearic acid monoglyceride, and 2.0 parts of glyceryl monostearate; The method for preparing the pressed board comprises the following steps: (a) mixing aluminum hydroxide particles with polyethylene glycol, paraffin, dihydroxy stearic acid monoglyceride and glyceryl monostearate, heating to 85° C. and stirring evenly; (b) cooling the mixture to room temperature under normal pressure, and then pressing and molding; (c) drying the formed pressed board at 160° C. for 3 hours to obtain the pressed board.

[0186] Experimental example This experimental example is a super-hard silicon-free material pressed plate, and the pressed plate is made of the following raw materials in parts by weight: 100 parts of aluminum hydroxide particles, 9.8 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, and 0.7 parts of antioxidant; The method for preparing the pressed board comprises the following steps: (a) adding oxidized polyethylene wax, coupling agent, maleic acid, aluminum hydroxide particles and antioxidant into an internal mixer according to weight ratio, melting at 160-165° C. for 3-4 minutes, stirring at a speed of 50-60 r / min for 0.6-1.8 hours, and spray cooling to obtain oxidized polyethylene wax additive; (b) mixing the obtained oxidized polyethylene wax additive with aluminum hydroxide particles, adding them according to a ratio, and then obtaining modified aluminum hydroxide particles after stirring and cooling; (c) mixing the modified aluminum hydroxide particles and the base fiber material in a weight ratio of 100:300-400, adding water glass in a weight ratio of 1:8-10 and mixing them evenly, and then molding the mixture to obtain a green body; (d) drying the green body at 200-230° C. for 0.6-1 hour, calcining it at 450-500° C. for 0.2-0.4 hour, isostatically pressing it at 1500-1700° C., and cooling it to room temperature to obtain a super-hard silicon-free material pressed plate.

[0187] Table 1 Hardness test results of three pressed boards

[0188] Table 2 Wear resistance test results of three pressed plates

[0189] From Table 1 and Table 2, we can see that: The ultra-hard silicon-free material pressed plate prepared in the experimental example is superior to the traditional silicon-free material pressed plates prepared in comparative examples 1 and 2 in terms of hardness and wear resistance, indicating that the technical solution has a significant effect in improving the ultra-hardness and wear resistance of the pressed plate.

[0190] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

[0191] The above descriptions are only some preferred embodiments of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present invention is not limited to the technical solutions formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the embodiments of the present invention.

Claims

1. A super-hard silicon-free material pressed plate, characterized in that: The invention comprises aluminum hydroxide particles, and the aluminum hydroxide particles are mixed and stirred with an auxiliary agent solution, and after sufficient reaction, filtered, washed and dried to obtain modified aluminum hydroxide particles. The auxiliary agent is prepared by mixing dihydroxystearic acid monoglyceride, glyceryl monostearate, paraffin, polyethylene glycol, water, glycerol and aluminum hydroxide particles. The weight ratio of the dihydroxystearic acid monoglyceride, glyceryl monostearate, paraffin, polyethylene glycol, water, glycerol and aluminum hydroxide particles is: 1-1.2 parts of dihydroxystearic acid monoglyceride, 1-2.5 parts of glyceryl monostearate, 1.8-2.3 parts of paraffin, 20-27 parts of polyethylene glycol, 6-10 parts of water, 1.2-1.5 parts of glycerol and 100 parts of aluminum hydroxide particles.

2. The ultra-hard silicon-free material pressed plate according to claim 1, characterized in that: The oxidized polyethylene wax is prepared from oxidized polyethylene wax and modified oxidized polyethylene wax; the modified oxidized polyethylene wax is a mixture of oxidized polyethylene wax modified by a coupling agent and oxidized polyethylene wax modified by maleic acid in a weight ratio of 2:1; the oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, the coupling agent, maleic acid, aluminum hydroxide particles and the antioxidant is: 9-10 parts of oxidized polyethylene wax, 8-10 parts of coupling agent, 6-8 parts of maleic acid, 11-15 parts of aluminum hydroxide particles and 0.5-1.0 parts of antioxidant.

3. The ultra-hard silicon-free material pressed plate according to claim 2, characterized in that: The modified oxidized polyethylene wax is prepared by spraying and mixing a silane coupling agent solution with a mass percentage of 1% and oxidized polyethylene wax in a weight ratio of 100:5-8, and cooling to 15°C at a speed of 5°C / s; the coupling agent is a 1% aminopropyltriethoxysilane solution.

4. The ultra-hard silicon-free material pressed plate according to claim 3, characterized in that: The coupling agent is an ethanol / water mixed solution of a water-soluble silane coupling agent with a mass percentage of 10%.

5. The ultra-hard silicon-free material pressed plate according to claim 4, characterized in that: The oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, the coupling agent, maleic acid, aluminum hydroxide particles and the antioxidant is: 10 parts of oxidized polyethylene wax, 10 parts of coupling agent, 8 parts of maleic acid, 15 parts of aluminum hydroxide particles and 1 part of antioxidant.

6. The ultra-hard silicon-free material pressed plate according to claim 5, characterized in that: The oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, the coupling agent, maleic acid, aluminum hydroxide particles and the antioxidant is: 9 parts of oxidized polyethylene wax, 9 parts of coupling agent, 7 parts of maleic acid, 12 parts of aluminum hydroxide particles and 0.5 parts of antioxidant.

7. The ultra-hard silicon-free material pressed plate according to claim 5, characterized in that: The oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, the coupling agent, maleic acid, aluminum hydroxide particles and the antioxidant is: 9.5 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 14 parts of aluminum hydroxide particles and 0.8 parts of antioxidant.

8. The ultra-hard silicon-free material pressed plate according to claim 7, characterized in that: The oxidized polyethylene wax is prepared from oxidized polyethylene wax, a coupling agent, maleic acid, aluminum hydroxide particles and an antioxidant, and the weight ratio of the oxidized polyethylene wax, the coupling agent, maleic acid, aluminum hydroxide particles and the antioxidant is: 9.8 parts of oxidized polyethylene wax, 8.5 parts of coupling agent, 6.5 parts of maleic acid, 13 parts of aluminum hydroxide particles and 0.7 parts of antioxidant.

9. The ultra-hard silicon-free material pressed plate according to claim 3, characterized in that: The diameter of the aluminum hydroxide particles is 0.2-0.6 mm.

10. The ultra-hard silicon-free material pressed plate according to claim 1, characterized in that: The coupling agent is a 1% by mass aminopropyltriethoxysilane solution.